Pharmacokinetics and safety of high-dose rifampicin in children with TB: the Opti-Rif trial - Garcia-Prats, Anthony J; Svensson, Elin M; Winckler, Jana; Draper, Heather R; Fairlie, Lee; van der Laan, Louvina E; Masenya, Masebole; Schaaf, H Simon; Wiesner, Lubbe; Norman, Jennifer; Aarnoutse, Rob E; Karlsson, Mats O; et al. (Journal of antimicrobial chemotherapy, 2021)
Rifampicin doses of 40 mg/kg in adults are safe and well tolerated, may shorten anti-TB treatment and improve outcomes, but have not been evaluated in children. To characterize the pharmacokinetics and safety of high rifampicin doses in children with drug-susceptible TB. The Opti-Rif trial enrolled dosing cohorts of 20 children aged 0-12 years, with incremental dose escalation with each subsequent cohort, until achievement of target exposures or safety concerns. Cohort 1 opened with a rifampicin dose of 15 mg/kg for 14 days, with a single higher dose (35 mg/kg) on day 15. Pharmacokinetic data from days 14 and 15 were analysed using population modelling and safety data reviewed. Incrementally increased rifampicin doses for the next cohort (days 1-14 and day 15) were simulated from the updated model, up to the dose expected to achieve the target exposure [235 mg/L·h, the geometric mean area under the concentration-time curve from 0 to 24 h (AUC0-24) among adults receiving a 35 mg/kg dose]. Sixty-two children were enrolled in three cohorts. The median age overall was 2.1 years (range = 0.4-11.7). Evaluated doses were ∼35 mg/kg (days 1-14) and ∼50 mg/kg (day 15) for cohort 2 and ∼60 mg/kg (days 1-14) and ∼75 mg/kg (day 15) for cohort 3. Approximately half of participants had an adverse event related to study rifampicin; none was grade 3 or higher. A 65-70 mg/kg rifampicin dose was needed in children to reach the target exposure. High rifampicin doses in children achieved target exposures and the doses evaluated were safe over 2 weeks.